Analysis of an accessibility strategy for deaf people: Videos on a traveling science center - Ferreira, Alessandra Teles Sirvinskas; Alves, Gustavo Henrique Varela Saturnino; Vasconcelos, Iara Alves Hooper; Souza, Thaís Varandas de Azeredo; Fragel-Madeira, Lucianne (Frontiers in Education, 2023)
Introduction Brazilian traveling science centers have difficulties in providing sign language accessibility to the deaf people that visit them. The main objective of this study was to analyze the contribution of accessible video guides in Brazilian Sign Language (BSL) in helping deaf visitors understand the activities proposed by the traveling science center “Ciências Sob Tendas”. Methods This research used a critical quali-quantitative approach that involved 128 deaf students from middle and high schools. Data were gathered via an online survey and video recording. Results and discussion The results indicated successful use of the video guides by deaf participants. Within this specific research, in which 745 questionnaires were answered, we found that the videos, along with interactive activities, contributed to the interest, curiosity, and understanding of the themes presented. Furthermore, the return visits of deaf people to revisit activities a second and third time may indicate the potential of this science communication strategy to stimulate their interest in scientific knowledge. However, 15% of responses showed that they had some difficulty understanding the video's explanation. This may indicate that, although videos are a well-accepted alternative for accessibility, the presence of an interpreter guide or a deaf visitor guide, when possible, is ideal. Essentially, a professional interpreter can use several BSL resources and strategies to make themselves understood. Conclusion Thus, we considered that accessible video guides in BSL are a viable resource for providing accessibility to deaf people in traveling science centers.